A Literature Review on the Use of Ethnomathematics-Based Student Worksheets in Elementary School Mathematics Learning - Via, Faricha Putri Alif; Khafid, Muhammad; Ellianawati, Ellianawati; Avrilianda, Decky (Universitas Negeri Semarang, 2025)
This study aims to analyze the trends, models, and effects of using ethnomathematics-based Student Worksheets in mathematics learning in elementary schools. The method used is a Systematic Literature Review by synthesizing 15 articles published between 2020 and 2025. Data analysis techniques were carried out using qualitative descriptive analysis with deductive and inductive reasoning to interpret and conclude the results of the study. The results of the analysis show that Research and Development studies dominate, integrating culture and mathematical material, such as geometry and arithmetic operations. Ethnomathematics-based LKPD can significantly improve students' mathematical concepts because it bridges abstract mathematical concepts to more concrete ones, making learning more meaningful and playing a role in instilling cultural values in students.